Pemilihan Karyawan Terbaik Menggunakan Metode Simple Additive Weighting (SAW) pada Perusahaan Investasi Emas - Anang Kurniawan; Reva Ragam Santika (Jurnal Informatika Universitas Pamulang, 2020)
In the assessment for the determination of the best employee is still done manually, and the lack of determination for the best employee. This study aims to build a decision support system for determining the best employees in accordance with what is expected by the company. The method used in this study is Simple Additive Weighting (SAW) with the provisions of predetermined criteria, namely, order, discipline, absenteeism, cooperation, creativity. This system was developed with the PHP programming language and also uses MySQL. From the results obtained manually accuracy with a percentage of 60%, While the results obtained from the accuracy of using the system reached 73.33%, namely the output of the system is able to choose one of the best employees. So, it can be concluded that this research can be used as a tool to determine the best employees so that the level of employee productivity can be better and can be beneficial for the company.